Movement integration in elementary classrooms: Teacher perceptions and implications for program planning. (April 2017) - Webster, Collin A.; Zarrett, Nicole; Cook, Brittany S.; Egan, Cate; Nesbitt, Danielle; Weaver, R. Glenn
Highlights: Elementary classroom teachers' perceptions of movement integration to increase children's physical activity were examined. Twelve first through third grade teachers across four schools participated in individual, semi-structured interviews. Findings centered on challenges/barriers, current and ideal resources, current implementation processes, and ideas and tips. This study provides important information for planning movement integration programs that are sensitive to teachers' needs. Abstract: Movement integration (MI), which involves infusing physical activity (PA) into regular classroom time in schools, is widely recommended to help children meet the national guideline of 60 min of PA each day. Understanding the perspective of elementary classroom teachers (ECTs) toward MI is critical to program planning for interventions/professional development. This study examined the MI perceptions of ECTs in order to inform the design and implementation of a school-based pilot program that focused in part on increasing children's PA through MI. Twelve ECTs (Grades 1–3) from four schools were selected to participate based on their responses to a survey about their use of MI. Based on the idea that MI programming should be designed with particular attention to teachers who integrate relatively few movement opportunities in their classrooms, the intent was to select the teacher who reported integrating movement the least at her/his respective grade level at each school. However, not all of these teachers agreed to participate in the study. The final sample included two groups of ECTs, including eight lowest integrating teachers and four additional teachers. Each ECT participated in an interview during the semester before the pilot program was implemented. Through qualitative analysis of the interview transcripts, four themes emerged: (a) challenges and barriers (e.g., lack of time), (b) current and ideal resources (e.g., school support), (c) current implementation processes (e.g., scheduling MI into daily routines), and (e) teachers' ideas and tips for MI (e.g., stick with it and learn as you go). The themes were supported by data from both groups of teachers. This study's findings can inform future efforts to increase movement opportunities for children during regular classroom time.